Suicide and Suicide Missions: Revisiting Durkheim [Suicidio y Misiones Suicidas: Revisitando a Durkheim] - Neira-Barrera, H (Universidad de Chile, Facultad de Ciencias Sociales, 2018)
We treat in this article the relation between the suicide mission and the concept of suicide. Suicide missions have become an important instrument of political struggle in present era. From the point of view of the attacker, suicide is a condition for the success of the action, and, from the point of view of the analysis, it is regulator concept, which allows understanding the relations between the individual and the society. Nevertheless, the concept of suicide might be insufficient or might be ideologically loaded. Because of this, it might render difficult to grasp the essential characteristics of that act. It will be necessary to examine, with contemporary criteria, some of the principal aspects of the notion of suicide defined by Durkheim, as well as the way in which the so-called theory of progress is a theoretic instrument politically used to discredit suicide missions. © 2018 Universidad de Chile, Facultad de Ciencias Sociales. All rights reserved.